Sunbelt/frostbelt : public policies and market forces in metropolitan development - Pack, Janet Rothenberg (Brookings Institution Press, 2005)
"The product of a multiyear project looking at how government policies shape growth patterns in five metropolitan areas--Los Angeles, Phoenix, Pittsburgh, Chicago, and Philadelphia--this book examines how these sunbelt and frostbelt metro areas have tried to use policy reform to address their individual development challenges"--Provided by publisher
Keywords: Metropolitan areas -- United States.; Metropolitan areas -- Government policy -- United States.; Regional planning -- United States.; Cities and towns -- United States -- Growth.; Aménagement du territoire -- États-Unis.; Villes -- États-Unis -- Croissance.; SOCIAL SCIENCE -- Sociology -- Urban.; BUSINESS & ECONOMICS -- Urban & Regional.; Cities and towns -- Growth; Metropolitan areas; Metropolitan areas -- Government policy; Regional planning; United States